2023
DOI: 10.1093/cid/ciad287
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Nirmatrelvir/Ritonavir on Coronavirus Disease 2019–Associated Hospitalization Prevention: A Population-based Cohort Study in the Province of Quebec, Canada

Abstract: Background The nirmatrelvir/ritonavir has shown to reduce COVID-19 hospitalization and death before Omicron but updated real-world evidence studies are needed. This study aimed to assess whether nirmatrelvir/ritonavir reduces the risk of COVID-19-associated hospitalization among high-risk outpatients. Methods This was a retrospective cohort study of SARS-CoV-2-infected outpatients between March 15 and October 15, 2022, using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Moreover, although NR was marketed for outpatient treatment of patients with mild to moderate disease at high risk of progression, some studies assessed the effect of NR on hospitalized patients 40,46,54,60–62 or did not exclude patients at standard risk for severe disease 35,36,38,40,43,45,57,61 . Nonetheless, our sensitivity analysis limiting the analysis to only the marketed patient population of high‐risk outpatients showed similar pooled RRs.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Moreover, although NR was marketed for outpatient treatment of patients with mild to moderate disease at high risk of progression, some studies assessed the effect of NR on hospitalized patients 40,46,54,60–62 or did not exclude patients at standard risk for severe disease 35,36,38,40,43,45,57,61 . Nonetheless, our sensitivity analysis limiting the analysis to only the marketed patient population of high‐risk outpatients showed similar pooled RRs.…”
Section: Discussionmentioning
confidence: 87%
“…Of the 32 included studies, 14 offered effect estimates separated by vaccination status. Definition of fully vaccinated patients differed by study; some studies offered data for basic vaccination (two doses or one dose of the vaccine by Johnson & Johnson) and boosted patients (received ≥3 doses or the Johnson & Johnson vaccine + ≥1 booster dose), 20,34–36,43,45,55,57,58,61,63 others merged the group of basic vaccination and boosted patients (received ≥2 doses) 39,46,47 . These differences between studies may be due to differences in vaccination timelines across countries, with some countries having had earlier access to vaccination than others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the randomized controlled study, numerous countries have granted emergency use authorization to nirmatrelvir-ritonavir for the management of COVID-19. Subsequently, a series of realworld studies [12][13][14][15][16][17] demonstrated the effectiveness of nirmatrelvir-ritonavir.…”
Section: Introductionmentioning
confidence: 99%